2021
DOI: 10.1186/s12905-021-01208-5
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic organ prolapse and uterine preservation: a cohort study (POP-UP study)

Abstract: Background Abdominal and laparoscopic sacro-colpopexy (LSC) is considered the standard surgical option for the management of a symptomatic apical pelvic organ prolapse (POP). Women who have their uterus, and for whom an LSC is indicated, can have a laparoscopic sacro-hysteropexy (LSH), a laparoscopic supra-cervical hysterectomy and laparoscopic sacro-cervicopexy (LSCH + LSC) or a total laparoscopic hysterectomy and laparoscopic sacro-colpopexy (TLH + LSC). The main aim of this study was to comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…Twelve studies reported treatment outcomes in 319 women (including women with a history of hysterectomy) with mesh erosion, and 77% (247/ 319) required re-operation for a mesh-related complication. 7,8,10,11,13,[15][16][17]27,28 Seven studies reported patientlevel data on those women with mesh erosion treated with conservative measures (n528), with 17 (61%) treated with expectant management, six (21%) treated with vaginal estrogen, and five (19%) treated with excision of mesh in the office. 8,10,11,15,16,27,28 In studies that reported mesh erosion, most did not stratify the level of complication associated with mesh erosion based on published classification systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies reported treatment outcomes in 319 women (including women with a history of hysterectomy) with mesh erosion, and 77% (247/ 319) required re-operation for a mesh-related complication. 7,8,10,11,13,[15][16][17]27,28 Seven studies reported patientlevel data on those women with mesh erosion treated with conservative measures (n528), with 17 (61%) treated with expectant management, six (21%) treated with vaginal estrogen, and five (19%) treated with excision of mesh in the office. 8,10,11,15,16,27,28 In studies that reported mesh erosion, most did not stratify the level of complication associated with mesh erosion based on published classification systems.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown a lower rate of mesh erosion when supracervical hysterectomy was performed compared with total hysterectomy, whereas others have noted no difference. [7][8][9][10][11][12][13][14][15][16][17][18][19] Expert consensus opinions have been conflicting, with a few stating that total hysterectomy concurrently performed with abdominal sacrocolpopexy should be avoided, whereas others indicate that further evaluation is necessary. 20,21 Yet, recent trends in the United States show almost equal proportions of concomitant supracervical hysterectomy compared with total hysterectomy being performed at the time of abdominal sacrocolpopexy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of cases with surgical failure in the anterior compartment was also higher in the subgroup with UP (10.7%) than in concomitant SCH (4.0%) in the present study. Our results with regard to anterior compartment failures were similar to those of Gagyor et al .,[ 22 ] who reported rates of 21.1% in cases undergoing UP and 8.8% in those undergoing SCH at 1 year postoperatively. Surgical failure in the posterior compartment was also more common in the UP subgroup (7.1%) than the SCH subgroup (2.3%) in our cohort, in contrast to the results of Gagyor et al .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical failure in the posterior compartment was also more common in the UP subgroup (7.1%) than the SCH subgroup (2.3%) in our cohort, in contrast to the results of Gagyor et al . [ 22 ] who reported posterior compartment failure rates of 0% in the UP group and 15.8% in the SCH group. Our UP subgroup showed no cases of apical compartment failure too, which only occurred in the SCH subgroup (1.7%).…”
Section: Discussionmentioning
confidence: 99%